The Trend of Mortality Rate and Years of Life Lost Due to Kidney Failure in Fars Province, Iran, During the Years 2004-2019 (Iranian Journal of Kidney Diseases, 2026)
Introduction. Chronic kidney disease is a general term for heterogeneous disorders that affect the structure and function of the kidney. This study was conducted to determine the mortality rate and years of life lost due to kidney failure in southern Iran. Method. In this retrospective, population-based descriptive trend study, all deaths due to kidney failure in Fars province were extracted from the electronic population-based death registration system (EDRS). The crude mortality rate, age-standardized mortality rate, years of life lost (YLL) and YLL rate data were calculated. The Joinpoint Regression method was used to examine the trend. Results. During the 16-year study period, 2853 deaths due to kidney failure occurred in Fars province. Of this number, 57.2% (1633 cases) were men. The crude mortality rate had a stable trend in men and an increasing trend in women. However, the age-standardized mortality rate had a stable trend in both sexes. The total years of life lost due to kidney failure were 19366 in men and 15769 in women. According to the Joinpoint regression analysis, the trend of YLL rate due to premature mortality was stable and the annual percent change (APC) were -2.6% (95% CI -5.6 to 0.4, P = .088) and 1.8% (95% CI -1.9 to 5.6, P = .318) for males and females respectively. Conclusions. The trend of crude mortality rate had a stable trend in men and an increasing trend in women. Also, the trend of YLL was stable for both sexes. The increasing trend in mortality among women may be due to increases in life expectancy and the increasing prevalence of non-communicable diseases such as hypertension and diabetes mellitus.